PENERAPAN SANITASI HIGIENE PADA KELOMPOK MINA SARI SEJAHTERA DI DESA PERANCAK KECAMATAN JEMBRANA, KABUPATEN JEMBRANA, BALI - Ni Made Ayu Suardani Singapurwa,; I Putu Candra,; I Nyoman Rudianta,; Ni Komang Armaeni, (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2021)
Community Service Activities were carried out at the Mina Sari Sejahtera Group in Perancak Village, Jembrana District, Jembrana Regency. The processing of fishery products has been produced and marketed by partners, but partners want to increase the quantity and quality. Partners do not yet have good processing knowledge and hygiene sanitation in processing, as well as inadequate processing facilities, so that production is not as desired. The solutions to solve the problems faced by partners are: providing Appropriate Technology in processing fish processing products; provide knowledge on good processing methods, sanitation and processing hygiene; providing equipment assistance, as well as providing assistance for repairing the floor of the processing area. The results of the activity show an increase in turnover of partners engaged in the economy, an increase in the quantity and quality of products, as well as an increase in people's understanding and skills